Otitis Media and Indigenous Australians - Williams, Cori (2003)
Otitis Media (OM) is a significant factor in the health of the indigenous population of Australia, and has the potential to affect the acquisition of language and literacy. Rates of OM in Indigenous Australians far exceed those in the non-Indigenous population, and the first episode of OM occurs early in life (Couzos, Metcalf & Murray, 2001). This paper reviews the literature regarding OM worldwide, and in the Indigenous Australian population, focusing on rates of occurrence and long-term outcomes for affected individuals. An extensive epidemiological investigation of OM in the Indigenous population of Western Australia is described.